New suffix array algorithms - linear but not fast? - Antonitio, A.; Ryan, P.; Smyth, Bill; Turpin, A.; Yu, X. (Australian Computer Society, 2004)
In 2003 three (-)(n)-time algorithms were proposed for the construction of a suffix array of a string x = x[1..n] on an indexed alphabet, all of them inspired by the methodology of Farach's (-)(n)- time suffix tree construction algorithm. In the same year a (-)(m)-time algorithm was described for computing all the occurrences of a pattern p = p[1..m] in x, given a suffix array of x and various other (-)(n) - space data structures. We analyze the effectiveness and limitations of these algorithms, especially in terms of execution time, and we discuss strategies for their improvement.